Tumor Enucleation vs. Partial Nephrectomy for T1 Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Xu, Congcong; Lin, Caixiu; Xu, Zhen; Feng, Sheng; Zheng, Yichun (Frontiers in Oncology, 2019)
Purpose: Tumor enucleation (TE) and partial nephrectomy (PN) have both become main treatment strategies for T1 renal cell carcinoma (RCC), despite the discrepancy between their safety margin. We performed a meta-analysis on all the relevant trials in order to compare the clinical efficacy and safety of TE with those of PN for RCC treatment. Methods: In this meta-analysis, randomized controlled trials or retrospective studies were included if they compared TE and PN therapy in patients with localized renal cancer. The main outcomes extracted were perioperative data and postoperative outcomes. Subgroups for analyses were undertaken according to tumor size and duration of follow up. Data were pooled using the generic variance method with a fixed or random effects model and expressed as mean differences or odds ratios with 95% CI. Results: A total of 13 studies containing 1792 patients undergoing TE and 3068 undergoing PN were identified. Our study showed that the patients received TE had significantly shorter operative time (MD = -28.46, 95% CI =-42.09, -14.83, P < 0.0001) , less hospital day (MD = -0.68, 95% CI =-1.04, -0.31, P = 0.0003), less estimate blood loss (MD = -59.90, 95% CI =-93.23, -26.58, P = 0.0004) and smaller change in estimated glomerular filtration rate (fixed effect: MD = 4.66, 95% CI =1.67, 7.66, P = 0.002), fewer complications (fixed effect: OR = 0.65, 95% CI =0.50, 0.85, P = 0.001) compared with those received PN. However, there were no significant differences in terms of warm ischemic time, positive margin rates, recurrence rates and survival rates between the two groups. All the subgroup analyses presented consistent results with the overall analyses. Conclusions: Our findings suggested that TE is not only was less-traumatizing and beneficial for recovery, but also better for renal function protection. Moreover, it didn’t show the evidence of an increase relapse rate or mortality rate when compared with PN.